MANAGEMENT OF A PATIENT WITH ATHEROSCLEROSIS AND ARTERIAL HYPERTENSION COMORBID WITH AN ASYMPTOMATIC PANCREATIC PSEUDOCYST ON THE EXAMPLE OF CLINICAL CASE - Oyebamire, I.; Oyebamire, M.; Belal, S. A. S.; Liuta, Е. А.; Vodyanitska, N. А. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Management of patients in therapeutic practice is becoming serious difficulties in view of the large prevalence of comorbidity pathologies of various organs and systems, especially atherosclerosis and arterial hypertension since these diseases is epidemic in recent years. Pancreatic pseudocyst is a localized fluid collection that is rich in amylase and other pancreatic enzymes and it presentation can be ranged from asymptomatic process to major abdominal catastrophe due to complications like infections, hemorrhages, obstruction and rupture. The main difficulty in the management of patients with pancreatic pseudocysts is a lack of effective medical and surgical treatment. Success can only be achieved with an individual approach to the patient with the joint cooperation of doctors of various profiles, as shown by our clinical case.